Coping with alternatives in sales organisations: Experiences from an Italian company - Andrea Perna; Silvio Cardinali; Gian Luca Gregori (jbm - Journal of Business Market Management, 2013)
This paper analyses the relevant aspects of the transition that must be addressed when companies operating in mature markets change from one sales structure to another. In our specific research context, we try to shed light on the transition between one sales configuration based on manufacturer's representatives (reps) to a different configuration set on the direct sales channel. The research uses a single case and exploratory method, focusing on the Italian firm Santarelli, which operates within the construction industry. Santarelli is a general contractor that also handles the sale and management of properties for residential and commercial use. After analysing its competitive context, Santarelli created its own sales offices, slightly veering away from its established network of intermediaries (real estate agencies). The general conclusion is that changing the sales organisation is a non-linear process: one way of managing complex changes is to keep business relationships alive within the business network.
urn:nbn:de:0114-jbm-v6i3.358
Keywords: 650; Sales Channel; Intermediary; Channel Shifting; Construction; Industry; Transition; Case Study